The changes of dietary fiber intake in obese adults: NCDs cohort study in Bogor City - Farida Dwi Rokhmah; Dodik Briawan; Ikeu Ekayanti; Sudikno Sudikno (AcTion: Aceh Nutrition Journal, 2023)
The prevalence of obesity in the adult is increasing each year due to increased consumption of fast food and decreased consumption of fiber.  Based on Basic Health Research there was 20% of Indonesians suffered from obesity in 2018. The objective is to analyze changes in dietary fiber intake in adult obese in Bogor City. Methods: This research is conducted using secondary data from Risk-Factor of Non-Communicable Disease Bogor. The research design was prospective cohort.  Total subjects were 138 subjects who were newly suffer from obesity in 2014 and 2016, and had normal BMI in baseline (2011 and 2012). Consumption data were collected using 24-hr recall and FFQ and were processed and analyzed using Nutri Survey, Microsoft excel and SPSS 23.0 version. Univariate analysis was used to see the characteristic of the subjects, while different test was using Wilcoxon test since the data are not distributed normally. Results,most subjects were women (77,5%) aged 35-44 years old. The mean of dietary fiber intake was at about 9,7 g in the beginning and it increased by 1,2 g. Despite the increment in the percentage of the people who consumed dietary fiber at about 58%, the mean was still under the recommendation (<25g) at 96,4%. Conclusions, there was an increasing number of dietary fiber in the obese adult who were newly suffered from obesity in two years follow-ups, but the intake is still under the recommendation.